(untitled) (Fiep Bulletin - online, 2015)
Compare Futsal players’ HRmax obtained in three different situations: competition (HR1), 220age equation (HR2), and maximal incremental test (HR3). Methods: Ten female athletes (161.0 3.8 cm height; 17.20 19.5 years; 23.7 4.4% body fat; 40.0 3.8 mLO2.kg-1.min-1 VO2max) belonging to a futsal team from Belo Horizonte that had won the 2002 Metropolitan Championship were evaluated. To measure HRmax during the matches and during the maximal incremental test, the volunteers used a Polar Vantage® heart rate monitor. HR1 was taken as the highest HR of each player during matches. HR2 was estimated using the following equation: HRmax = (220 age). HR3 was determined as the highest HR recorded during a maximal incremental test until fatigue performed on a bicycle ergometer. Wilcoxon Rank Sum and Pearson Chi-Square tests were used in statistical analysis with significance level of p<0.05. Results: HR2 (200 2 bpm) was higher than HR3 (187 14 bpm), p<0.05. HR1 (198 11 bpm) was not different from either HR2 or HR3. There was no significant correlation between variables HR1, HR2, and HR3. We observed that competition HRmax presented higher absolute values for 8 of the 10 athletes evaluated when compared to test HRmax. Conclusion: HRmax measurements during standardized tests performed in laboratory may be underestimated in relation to competition values. This may be due to the fact that the tests represent an artificial situation for the athletes, who do not feel as motivated as during competitions. Due to the high individual variation of HRmax, it would be preferable to measure it either in laboratory tests or during competition instead of estimating it using the (220 - age) equation.